The Linguistics of Faith: Understanding the Human-God Relationship in Javanese and Arabic Expressions - Hendrokumoro; Arief Budiman; Imam Wicaksono; Nadia Khumairo Ma'shumah; Vina Hidayah (OKARA: Jurnal Bahasa dan Sastra, 2025)
Language functions not only as a means of communication, but also as a medium that represents a society's worldview and spiritual values. Within this context, religious expressions in Javanese and Arabic reflect the ways in which societies perceive the relationship between humans and God. This study examines the similarities in linguistic representation and philosophical meaning in these expressions. This study used a mixed-methods approach, integrating qualitative linguistic and hermeneutic analyses with descriptive quantitative analysis. The research data consisted of 39 expressions related to divine attributes, which portrayed the relationship between humans and God, gathered from written Javanese texts and verses from the Qur’an and Arabic wisdom expressions. The data were obtained through documentation technique and analyzed by identifying the lexemes, syntactic structures, and the philosophical meanings reflected in the expressions. The findings reveal those expressions in both languages indicate four underlying philosophical meanings: reverence, submission, devotion, and humility. These meanings are reflected in the occurrence of identical or synonymous lexicons and in the syntactic structures of both languages. Findings of this study demonstrate conceptual harmony in interpreting the vertical relationship between humans and God, which also illustrates the historical and cultural interaction between Javanese traditions and Islamic teachings. This study provides a contribution to linguistic and hermeneutic studies, particularly in understanding language as a medium that represents the religious values and philosophical views of society.